Vṛddhā-Kumārī: Establishment of a Sacred Landscape Through Ascetic Fervor - Garbanzo Pizarro, Vanessa (2025)
The Vṛddhā-kumārī is a female character who is the protagonist of one of the subtales that make up the whole of what the Mahābhārata entails. She is a woman who dedicates her life to asceticism and whose life is tied to a physical place, therefore, having permanent consequences in it. This work analyzes her experiences from its Sanskrit source (MBh, 9.51) and explores the role of ascetic fervor in the transformation of the natural landscape into a sacred one, in addition to highlighting the cultural value of the forest as a place of retreat and the tīrtha as a place of connection with the divine.